675.DETERMINING OPTIMAL ORDER PICKING ROUTE IN WAREHOUSES - Anita, Vasileva; Igor, Gjurkov (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2024)
The objective of this research paper is to find the optimal order picking route thus improving the operational efficiency of logistics processes. Computing and selecting the best route are crucial for minimizing order completing time and operational costs. To achieve this, an algorithm is developed by use of several warehouse logistics methods. This algorithm is applied to a single warehouse and the paths are computed using the s-method, the return method, the middle point method, and the composite method. The verification of the algorithm is conducted through thirty cases, each with different order picking locations. This research shows that when larger number of parts need to be picked from various racks, the paths created by the composite method and the s-method provide the shortest route for the designated warehouse.